2015
DOI: 10.1182/blood-2015-05-643601
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of glucocorticoid-associated osteonecrosis in children with acute lymphoblastic leukemia

Abstract: Key Points Comprehensive study of glucocorticoid-induced osteonecrosis identifies glutamate receptor gene variants as risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 48 publications
1
113
0
Order By: Relevance
“…6,9,[65][66][67][68] Polymorphisms in the plasminogen activator inhibitor-1 (PAI-1) gene were initially reported to be associated with an increased risk of osteonecrosis, 4,66 but this finding could not be confirmed by subsequent GWAS studies. 68 Osteonecrosis in children with ALL haematologica | 2016; 101(11) Likewise, findings about polymorphisms involved in lipid homeostasis (acid phosphatase locus 1, ACP1), 6 antifolate pharmacodynamics (thymidylate synthetase, TYMS), and steroid hormone response (vitamin D receptor, VDR), have been reported to be associated with osteonecrosis, 9 but were not reproducible in GWAS studies. 68 According to recent GWAS studies, the glutamate receptor pathway seems to be of crucial importance for the pathogenesis of osteonecrosis in patients with prolonged exposure to corticosteroids.…”
Section: Genetic Risk Factorsmentioning
confidence: 77%
See 2 more Smart Citations
“…6,9,[65][66][67][68] Polymorphisms in the plasminogen activator inhibitor-1 (PAI-1) gene were initially reported to be associated with an increased risk of osteonecrosis, 4,66 but this finding could not be confirmed by subsequent GWAS studies. 68 Osteonecrosis in children with ALL haematologica | 2016; 101(11) Likewise, findings about polymorphisms involved in lipid homeostasis (acid phosphatase locus 1, ACP1), 6 antifolate pharmacodynamics (thymidylate synthetase, TYMS), and steroid hormone response (vitamin D receptor, VDR), have been reported to be associated with osteonecrosis, 9 but were not reproducible in GWAS studies. 68 According to recent GWAS studies, the glutamate receptor pathway seems to be of crucial importance for the pathogenesis of osteonecrosis in patients with prolonged exposure to corticosteroids.…”
Section: Genetic Risk Factorsmentioning
confidence: 77%
“…Mechanical load opens mechanosensitive calcium channels in osteocytes, leading to exocytosis of glutamate, which activates osteoblast receptors and impairs endothelial barrier function. [67][68][69][70] In addition, SNPs in adipogenesis pathways and in enhancers active in mesenchymal stem cells are significantly associated with osteonecrosis development. 67 Bone morphogenetic protein (BMP) is toxic to vascular smooth muscle and is released in response to bone damage and mechanical stress.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] However, age remains the strongest and most consistently identified factor, with patients 10 to 20 years old at greatest risk. 10,11,[13][14][15] Given this age-related risk, the majority of children in prior investigations of genetic predisposition to osteonecrosis were .10 years. 10,15 However, because ALL is so common in young children, up to 40% of osteonecrosis cases develop in children ,10 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…10,11,[13][14][15] Given this age-related risk, the majority of children in prior investigations of genetic predisposition to osteonecrosis were .10 years. 10,15 However, because ALL is so common in young children, up to 40% of osteonecrosis cases develop in children ,10 years of age. 10 In this study, we identified genetic factors associated with the development of osteonecrosis in the largest cohort of SR ALL patients evaluated to date and validated these findings in a cohort of NCI highrisk ALL patients ,10 years of age.…”
Section: Introductionmentioning
confidence: 99%